Professional Image Maintenance: How Women Navigate Pregnancy in the Workplace - Little, Laura M.; Major, Virginia Smith; Hinojosa, Amanda S.; Nelson, Debra L. (Academy of Management Journal, 2015)
Women now constitute a significant portion of the workforce, making the effects of pregnancy on professional image (others' perceptions of competence and character at work) more salient. While opinions regarding how pregnant women should manage others' impressions and the consequences of doing so abound (Noveck, 2012) research to substantiate or disconfirm these opinions has lagged. In this paper, we present three studies that develop and test a model of social identity-based impression management (SIM) techniques used by pregnant workers. In Study 1 (n = 35), we utilized qualitative methods to identify the motives and strategies used by pregnant women to manage their professional images. In the second study, we collected two samples (n = 199 and n = 133) to develop and validate two scales based on the motives and strategies identified in Study 1. In Study 3 (n = 200), we employed a time-lagged design to examine how SIM motives and strategies affect important workplace outcomes: perceived discrimination, burnout, and returning to one's job after maternity leave. Our findings demonstrate both positive and negative outcomes of the motives and strategies women use to manage their images at work when pregnant.